2017
DOI: 10.1016/j.maturitas.2017.07.014
|View full text |Cite
|
Sign up to set email alerts
|

27-Hydroxycholesterol, an endogenous selective estrogen receptor modulator

Abstract: Estrogen receptors (ERs) mediate the actions of the steroidal estrogens, and are important for the regulation of several physiological and pathophysiological processes, including reproduction, bone physiology, cardiovascular physiology and breast cancer. The unique pharmacology of the ERs allows for certain ligands, such as tamoxifen, to elicit tissue- and context-specific responses, ligands now referred to as selective estrogen receptor modulators (SERMs). Recently, the cholesterol metabolite 27-hydroxychoels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 103 publications
(126 reference statements)
4
37
1
Order By: Relevance
“…In poorly differentiated cancers, ERα was not detected consistent with previous reports (Collins et al 2009). It has been reported that 27HC, acting as a SERM, can impact on ERα-or ERβ1-dependent regulation of cell function (He & Nelson 2017) and the oestrogenic effects of 27HC could therefore be mediated via either ER isoform in EC cells. In endometrial endothelial cells, which express ERβ but not ERα, oestrogenic effects are mediated via ERβ tethered to Sp1 and not via direct binding to ERE (Greaves et al 2013).…”
Section: :4supporting
confidence: 88%
“…In poorly differentiated cancers, ERα was not detected consistent with previous reports (Collins et al 2009). It has been reported that 27HC, acting as a SERM, can impact on ERα-or ERβ1-dependent regulation of cell function (He & Nelson 2017) and the oestrogenic effects of 27HC could therefore be mediated via either ER isoform in EC cells. In endometrial endothelial cells, which express ERβ but not ERα, oestrogenic effects are mediated via ERβ tethered to Sp1 and not via direct binding to ERE (Greaves et al 2013).…”
Section: :4supporting
confidence: 88%
“…However, this data is only visualized when expressed as urinary output, and not perceptible as excretion fraction of calcium. There has been shown that menadione (MEN) or vitamin K3, inhibits transiently the intestinal Ca 2+ absorption in normal chicks and rats [34,35]. Although not measured by us, is plausible to assume that the OVX animals may exhibit negative calcium balance, which may also enhanced by VK treatment, resulting into lower BMD found in this group when compared to SHAM animals.…”
Section: +mentioning
confidence: 82%
“…It is well known that for nucleation of hydroxyapatite into organic bone matrix two fundamental factors are necessary: abundance of y-carboxylase in liver and/or osteoblast, delivery of enough amounts of Ca 2+ and Pi to bone, and y-carboxylation of GLA -protein, such as osteocalcin [34,35]. Therefore we measured hyper (three) y-glutamic acid carboxylated plasma osteocalcin (HYP-OC) in our experimental groups (Fig.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…17β-estradiol has been reported to inhibit metastasis-associated lung adenocarcinoma transcript 1 (MALAT-1)-mediated osteosarcoma migration, invasion, metastasis, and induction of cell apoptosis, in an estrogen receptor α (ERα)-independent manner [15]. Earlier it was thought that binding of ER agonists induces a conformational change in the receptors, conferring the ability for coactivators to bind, whereas ER antagonists were thought to compete for binding [52]. But later studies with tamoxifen revealed that the same molecule can behave as an agonist (tamoxifen acts as an estrogen agonist in the uterus, promoting hypertrophy) as well as an antagonist (tamoxifen exhibited estrogenic activity in the bone, thus protecting against bone loss), depending on the tissue context.…”
Section: Selective Estrogen Receptor Modulators (Serms)mentioning
confidence: 99%
“…However, their different affinities for the different subtypes of ERs (α and β) and different relative expressions of these subtypes in tissues may explain some the of SERMs' pharmacology. Recent evidence also suggests that binding of the receptor even by structurally related compounds could result in unique conformational changes, thus allowing recruitment of distinct sets of co-activators and/or corepressors to the receptor [52].…”
Section: Selective Estrogen Receptor Modulators (Serms)mentioning
confidence: 99%